2014
DOI: 10.1177/0003489414523562
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Cholesteatoma Surgery

Abstract: The results of this study demonstrate that CWDT with mastoid obliteration resulted in a quality of life comparable with that after ICWT. Postoperative hearing loss is the most frequently reported problem for both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In our study, we demonstrated the absence of a significant difference, in terms of self-perceived quality of life, in patients undergoing CWU compared to CWD. Our results are consistent with those reported by other authors 91216 . The study conducted by Lailach et al 16 which compared QoL outcomes among CWD, CWU and exclusively transcanalar technique (ETC) demonstrated that CWD showed similar results in QoL compared to CWU, whereas the ETC group reported significantly higher performances.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, we demonstrated the absence of a significant difference, in terms of self-perceived quality of life, in patients undergoing CWU compared to CWD. Our results are consistent with those reported by other authors 91216 . The study conducted by Lailach et al 16 which compared QoL outcomes among CWD, CWU and exclusively transcanalar technique (ETC) demonstrated that CWD showed similar results in QoL compared to CWU, whereas the ETC group reported significantly higher performances.…”
Section: Discussionsupporting
confidence: 94%
“…All previous scientific comparisons, however, were conducted on CWD with mastoid obliteration versus CWU. Accordingly, it is suggested that the overlapping results are due to a decreased incidence of neo-mastoid cavity disadvantages in the CWD group 891617 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of a questionnaire or the systematic questioning of patients regarding their symptoms does not yet appear to be general practice. The national cholesteatoma study and the literature ( 16 , 17 ) show that hearing loss with or without otorrhea is the most important health concern. In addition, to improve hearing, the cessation of otorrhea is a determining factor for the success of surgery according to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto studies have either applied general health questionnaires to COM patients or compared mucosal and squamosal COM with disease-specific questionnaires. Quaranta et al reported comparable scores on QOL scores following CWU and CWD with mastoid obliteration [19].…”
Section: Quality Of Life In Chronic Otitis Mediamentioning
confidence: 96%